ANÁLISE MULTICRITERIAL APLICADA A ELABORAÇÃO DE ZONEAMENTO DE UNIDADE DE CONSERVAÇÃO NA ZONA COSTEIRA DA BAHIA, BRASIL - Do Nascimento Lopes, Elfany Reis [UNESP]; Lourenço, Roberto Wagner [UNESP]; Reuss-Strenzel, Gil Marcelo (Universidade Federal do Paraná, 2016)
This study aimed to demonstrate the application of multicriterial analysis (MCA) in the zoning of protected areas located in the coastal zone of Brazil, using the Environmental Protected Area (EPA) of Guaibim (Valença-Bahia), as an example in a zoning that combines conservation of natural resources and local development. The multicriterial analysis was used to fit the EPA to the conservation and development through the establishment of criteria originated of a map of land use and the weighting of importance weights by process of hierarchical analysis technical and aggregation of factors by the linear weighted combination technical. The map of viability for conservation presented higher scores of viability in territorial extremes with mangrove, swamps, sandbanks areas and rivers. The map of viability for development suggested higher scores to the center of the EPA. Later, the generated maps were integrated by the multiple-objective analysis, by eliminating conflicts and accommodating appropriate areas for each objective. The multiple-objective analysis suggested that approximately 70% of the area for the conservation and development was delimited to 30% of the territory, culminating in two main areas of management (Conservation Area and Area of Development) and management subareas. The AMC is an analysis indicated the preparation of zoning of protected areas or, in its update, with ample capacity to reflect the reality of the territory and assist in conflict resolution during the decision process.
Multicriteria analysis applied to zoning of protected areas in the coastal zone of Bahia, Brazil
Keywords: Decision-making; Geographic information system; Management zones; Multiple-objective analysis